2018
DOI: 10.1371/journal.pone.0193168
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of infected lungs by ex vivo perfusion with high dose antibiotics and autotransplantation: A pilot study in pigs

Abstract: The emergence of multi-drug resistant bacteria threatens to end the era of antibiotics. Drug resistant bacteria have evolved mechanisms to overcome antibiotics at therapeutic doses and further dose increases are not possible due to systemic toxicity. Here we present a pilot study of ex vivo lung perfusion (EVLP) with high dose antibiotic therapy followed by autotransplantation as a new therapy of last resort for otherwise incurable multidrug resistant lung infections. Severe Pseudomonas aeruginosa pneumonia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
0
30
0
1
Order By: Relevance
“…No solution is currently designed for perfusion preservation and typical substrates, such as glucose, may be ineffective to support myocardial metabolism during cold perfusion . Ex vivo perfusion systems for lung transplantation have already been used to treat aspiration pneumonitis, pneumonia, and pulmonary thromboembolic disease . Experimental evidence also suggests delivery of anti‐inflammatory cytokines, gene products, and other therapeutic agents is feasible to repair donor organs or reduce injury sustained by the graft during preservation––thus increasing the donor pool and improving results after transplantation …”
Section: Current and Near‐term Application Of Machine Perfusion Presementioning
confidence: 99%
“…No solution is currently designed for perfusion preservation and typical substrates, such as glucose, may be ineffective to support myocardial metabolism during cold perfusion . Ex vivo perfusion systems for lung transplantation have already been used to treat aspiration pneumonitis, pneumonia, and pulmonary thromboembolic disease . Experimental evidence also suggests delivery of anti‐inflammatory cytokines, gene products, and other therapeutic agents is feasible to repair donor organs or reduce injury sustained by the graft during preservation––thus increasing the donor pool and improving results after transplantation …”
Section: Current and Near‐term Application Of Machine Perfusion Presementioning
confidence: 99%
“…For example, it was shown that donor lungs impaired by aspiration of gastric acid can be treated with lavage and surfactant replacement during EVLP . Similarly, in the case of donor lung infection, antibiotics will be delivered in the EVLP system at high doses to avoid systemic toxicity . Other preclinical studies show that hepatitis C virus can be cleared from donor lungs using a combination of ultraviolet irradiation and photodynamic therapy during EVLP, similar to the means used in blood banks to sterilize donor blood components .…”
Section: Long‐term Futurementioning
confidence: 99%
“…17 Similarly, in the case of donor lung infection, antibiotics will be delivered in the EVLP system at high doses to avoid systemic toxicity. 18 Other preclinical studies show that hepatitis C virus can be cleared from donor lungs using a combination of ultraviolet irradiation and photodynamic therapy during EVLP, similar to the means used in blood banks to sterilize donor blood components. 19 Moreover, we anticipate that in the long-term future, EVLP will be used to go beyond the treatment of impaired donor lungs to actually enhance the donor lungs beyond their physiological function.…”
Section: Mid-term Futurementioning
confidence: 99%
“…Our hypothetical treatment approach for this obvious military medical challenge is outlined in this paper. Recently, there has been growing evidence for the successful application of ex vivo perfusion in solid organ transplantation [13][14][15][16][17]. Figure 1 shows the basic scheme of a machine perfusion system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the reduction of the cold ischemic time, ex vivo organ perfusion systems can be used for extended criteria donor organs due to an improvement of graft function during machine perfusion. Individualized organ therapy is possible following the reevaluation of the organ [17]. It can be assumed that ex vivo organ perfusion is able to relieve the donor organ shortage.…”
Section: Introductionmentioning
confidence: 99%